The influence of financial ratios on non performing financing of the sharia rural banks of Special Region of Yogyakarta (BPRS DIY) period 2015 – 2018 - Taufikur Rahman; Khusna Fatmawati (Asian Journal of Islamic Management (AJIM), 2020)
Purpose: This study aims to analyze the effect of financial performance on Non-Performing Financing of Sharia Rural Banks (BPRS) in the Special Region of Yogyakarta (DIY). This study provides an empirical contribution as research that adds evidence in the financial sector, especially banking risks related to the determinants of Non-Performing Financing of Sharia rural banks in DIY in 2015-2018.Methodology: Research data were obtained from quarterly financial reports at the Financial Services Authority for the period 2015 to 2018 with a research sample of 9 BPRS.Findings: The results of the findings show that return on assets (ROA) and operating income operating expenses (BOPO) which have a significant effect on non-performing financing. Meanwhile, return on equity, financing to deposit ratio, and capital adequacy ratio does not have a significant effect on the non-performing financing of BPRS in DIY.Originality/Value: To the author's knowledge, as the variations of the results among researchers exist, the findings of this research provides deeper insight into the literature of Non Performing Financing Bank regarding its financial ratio.